Varieties of neo-colonialism: Government accounting reforms in Anglophone and Francophone Africa – Benin and Ghana compared. (December 2019) - Lassou, Philippe J.C.; Hopper, Trevor; Tsamenyi, Mathew; Murinde, Victor
Abstract: This study compares government accounting reforms in an Anglophone and a Francophone African country, namely Ghana and Benin, with respect to neo-colonialism. The data draws from interviews with local officials concerned with government accounting, documents and documentaries. The focus lay on the perceived effectiveness of reforms, and their formulation and implementation. In both countries their former colonial powers, Britain and France, still influence accounting through economic means (through monetary systems), international financial institutions, political advisors, Northern accounting associations and neo-patrimonialism. However, their use of these differs. While France structures her control mostly around the monetary system established during colonialism, Britain relies on its post-colonial infrastructure and accounting profession, and concedes much influence to the USA, essentially through international financial institutions. France exerts more direct control through advisors than Britain (with the USA). The French approach is conceptualized as coercive-neo-colonialism and the British as soft-neo-colonialism. Despite international financial institutions' pervasive presence, they are not monolithic agents with a uniform role and influence in Ghana and Benin, and good governance aims to increase civil service capacity, financial transparency and accountability remain problematic.